Complications after aortic arch hybrid repair - Geisbüsch, Philipp; Kotelis, Drosos; Müller-Eschner, Matthias; Hyhlik-Dürr, Alexander; Böckler, Dittmar (Journal of vascular surgery, 2011)
Objectives - To analyze early and midterm complications after hybrid aortic arch repair (HAR). Methods - Between January 1997 and November 2009 among 259 patients receiving thoracic endovascular aortic repair, HAR has been performed in 47 patients (median age, 64.5 years; range, 41-84). A retrospective analysis was performed. Complete supra-aortic debranching was performed in 15 patients (32%) and partial debranching in 23 patients (49%). Isolated left subclavian artery revascularization prior to thoracic endovascular aortic repair has been used in nine patients (19%). Emergency procedures were performed in 34% of all patients. - Results - The overall in-hospital mortality was 19% (9/47 patients), 27% after complete and 15.6% after partial debranching. Postoperative complications occurred in 32 patients (68%). Cardiocirculatory complications were observed in seven patients (15%). Pulmonary complications occurred in 12 patients (26%). A total of five patients (11%) experienced renal complications requiring hemodialysis. The stroke rate was 6.3%. Paraplegia was seen in three patients (6%). Proximal type I endoleaks were observed in seven patients. Retrograde aortic arch dissection was seen in three patients (6.3%). Cox proportional hazard regression showed the necessity for an emergency procedure as an independent predictor of death (hazard ratio, 2.9; 95% confidence interval, 1.1-7.5; P = .023). The reintervention rate was 27.6% with three patients requiring open conversion. - Conclusions - Hybrid aortic arch repair in high-risk patients is associated with a relevant morbidity, mortality, and reintervention rate. Patient selection is crucial and indication should be limited to patients not suitable for conventional aortic arch repair or emergency cases at present. Therefore, we recommend performing HAR only in high-volume centers with cardiovascular surgical cooperation.